1994 World Economic and Financial Surveys; Official Financing for Dev. Countries : Official Financing for Dev. Countries. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1994)
This paper focuses mainly on official bilateral and multilateral financing for countries that have rescheduled their debts to official bilateral creditors. In contrast to the approaches taken by private lenders, official creditors have continued to provide new financing on a large scale to countries with debt-servicing difficulties that implement adjustment and reform programs. Financial support bas been provided through a wide variety of instruments and channels. For the low-income rescheduling countries as a group, total financial assistance has been about as large as these countries' own export earnings in every year since 1986. The recent trends in official financing have important ramifications for developing countries. Access to external financing from official sources is likely to remain high for those countries whose adjustment and reform efforts provide assurances that resources will be used efficiently. Conversely, countries with uneven records of policy implementation (particularly as regards payments arrears) are likely to find difficulty in attracting financial support.